2020
DOI: 10.1111/head.13994
|View full text |Cite
|
Sign up to set email alerts
|

No “Wearing‐Off Effect” Seen in Quarterly or Monthly Dosing of Fremanezumab: Subanalysis of a Randomized Long‐Term Study

Abstract: Objective.-To evaluate whether quarterly or monthly administration of fremanezumab for migraine prevention exhibits a pattern of decreased efficacy toward the end of the dosing interval (wearing-off effect). Background.-The main goals of migraine preventive treatment are to reduce the frequency, severity, and duration of migraine attacks, and migraine-associated disability. Wearing-off refers to the phenomenon whereby clinical symptoms return or worsen before the next dose of a drug is due and has been reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 28 publications
0
19
0
2
Order By: Relevance
“…For all monoclonal antibodies targeting the CGRP pathway, efficacy seen during 12 weeks of double-blind treatment was maintained during longer term treatment. An analysis of data from the fremanezumab long-term study in patients with CM or EM confirmed that there was no evidence of a “wearing-off” effect toward the end of dosing intervals with either quarterly or monthly dosing; there was no increase in the mean number of weekly migraine days between the first 2 weeks and last 2 weeks of quarterly or monthly dosing intervals throughout a total 15 months of treatment [ 42 ]. Similarly, an analysis of data from the 6-month EVOLVE-1 and -2 studies of galcanezumab in patients with EM and the 3-month REGAIN study of galcanezumab in patients with CM, showed no evidence of “wearing off” toward the end of the monthly dosing interval; reductions in migraine days during the first 2 weeks were comparable to those during the last 2 weeks of each month of treatment [ 43 ].…”
Section: Efficacy Of Cgrp Pathway-targeted Treatments In Migraine Pre...mentioning
confidence: 99%
“…For all monoclonal antibodies targeting the CGRP pathway, efficacy seen during 12 weeks of double-blind treatment was maintained during longer term treatment. An analysis of data from the fremanezumab long-term study in patients with CM or EM confirmed that there was no evidence of a “wearing-off” effect toward the end of dosing intervals with either quarterly or monthly dosing; there was no increase in the mean number of weekly migraine days between the first 2 weeks and last 2 weeks of quarterly or monthly dosing intervals throughout a total 15 months of treatment [ 42 ]. Similarly, an analysis of data from the 6-month EVOLVE-1 and -2 studies of galcanezumab in patients with EM and the 3-month REGAIN study of galcanezumab in patients with CM, showed no evidence of “wearing off” toward the end of the monthly dosing interval; reductions in migraine days during the first 2 weeks were comparable to those during the last 2 weeks of each month of treatment [ 43 ].…”
Section: Efficacy Of Cgrp Pathway-targeted Treatments In Migraine Pre...mentioning
confidence: 99%
“…Un estudio (n = 1.890) ha analizado específicamente esta cuestión seleccionando la variable días de migraña a la semana (DMS). Se realizaron las siguientes comparaciones en los meses 3, 6, 9 y 15 58 :…”
Section: Análisis Del Efecto Wearing-offunclassified
“…In placebo-controlled clinical trials, fremanezumab treatment was associated with reduced headache frequency, severity and duration in patients with CM or EM, including patients with acute medication overuse and patients with difficult-to-treat migraine, such as those with inadequate response to 2-4 classes of migraine preventive medications [19][20][21][22][23]. In a long-term extension study following the pivotal 3-month studies of fremanezumab in CM and EM, efficacy was maintained for a further 12 months of treatment, with no evidence of wearing off at the end of the quarterly or monthly dose intervals [18,24]. Additionally, patients reported high levels of treatment satisfaction, as well as improvements in sleep quality, reduced anxiety and increased quality of time spent with others [25].…”
Section: Background and Rationalementioning
confidence: 99%